NURSING CONSULTATION IN PRIMARY CARE: FROM THE BEGINNING OF PRAXIS TO DAILY LIFE - Silva e Lima, Stella Godoy [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP]; Spagnuolo, Regina Stella [UNESP] (Revista Baiana de Enfermagem, 2023)
Objective: to understand the meaning of nursing consultation from graduation to professional practice. Method: a qualitative study anchored in the Grounded Theory, with a sample of 14 nurses working in the Family Health Strategy, who were interviewed by open technique not directive in the years 2017 to 2018 and approved by the ethics committee. Three codifications were used to discuss the data, being open, axial and selective, which originated phenomena, themes, categories and subcategories organized based on the paradigm of Strauss and Corbin. Results: data analysis enabled the identification of the phenomenon called “From the beginning of praxis to the daily life of the NC” and the themes “The nursing consultation organizing the work process of the nurse” and “The presentation of the nursing consultation to the nurse”. Final considerations: the nursing consultation is considered the most important activity of the nurse's praxis.
CONSULTA DE ENFERMERÍA EN LA ATENCIÓN PRIMARIA: DEL INICIO DE LA PRAXIS AL COTIDIANO
CONSULTA DE ENFERMAGEM NA ATENÇÃO PRIMÁRIA: DO INÍCIO DA PRÁXIS AO COTIDIANO